Human health as a motivator for climate change mitigation: results from four European high-income countries. (July 2019) - Amelung, Dorothee; Fischer, Helen; Herrmann, Alina; Aall, Carlo; Louis, Valerie R.; Becher, Heiko; Wilkinson, Paul; Sauerborn, Rainer
Abstract: Invoking health benefits to promote climate-friendly household behavior has three unique advantages: (i) health co-benefits accrue directly to the acting individual, they are "private goods" rather than public ones; (ii) the evidence base for, and magnitude of health co-benefits is well-established; and (iii) the idea of a healthy life-style is well-engrained in public discourse, much more so than that of a climate-friendly life-style. In previous research, assessing the influence of information on health effects on people's motivation to adopt mitigation actions, health co-benefits for the individual were typically confounded with collective health co-benefits, for example from pollution reduction. The present research aims to overcome this limitation by providing information on individual health co-benefits that are unconditional on the actions of others ( direct health co-benefits ). We report effects of this kind of health information on stated willingness to adopt mitigation actions as well as on simulation-based carbon emission reductions in a pre-registered experimental setting among 308 households in 4 mid-size case-study cities in 4 European high-income countries: France, Germany, Norway and Sweden. For each mitigation action from the sectors food, housing, and mobility, half of the sample received the amount of CO2 equivalents (CO2 -eq) saved and the financial costs or savings the respective action generated. The other half additionally received information on direct health co-benefits, where applicable. For households receiving information on direct health co-benefits, we find a higher mean willingness to adopt food and housing actions, and a greater proportion very willing to adopt one or more mitigation actions (OR 1.86, 95% CI 1.1, 3.12); and a greater simulated reduction in overall carbon footprint: difference in percent reduction -2.70%, (95% CI -5.34, -0.04) overall and -4.45%, (95% CI -8.26, -0.64) for food. Our study is the first to show that providing information on strictly unconditional, individual health co-benefits can motivate households in high-income countries to adopt mitigation actions.